Forms, Models and Mechanisms of Public-Private Partnerships in the Service Sector - Utemuratova Gulnarakhan Khojaniyazovna, (Research Parks Publishers, 2023)
In this article, the forms of public-private partnership, the main directions of economic activity between state and private business entities, the economic content, goals and objectives, structure and models of the